Intergenerational and Marriage Mobility of University Professors in the Netherlands During the 19th Century - Ineke Maas; Marco H. D. van Leeuwen; Antonie Knigge (Historical Life Course Studies)
In this study we ask the question to what extent 19th-century university professors were a closed occupational group in the sense that they had little intergenerational and marriage mobility. We do so in honor of Kees Mandemakers, who is about to retire as a professor, but whose younger family members may follow in his footsteps. We derive competing hypotheses from cultural capital theory and the meritocracy thesis and test them using civil marriage records for the period 1813–1922 in six Dutch provinces (N = 1,180,976 marriages). Although only 4.4% of all university professors had a father in the same occupation, the odds ratio of 331 shows that this is much more likely than to be expected under independence. Similarly, professors were much more likely to marry the daughter of a professor. Compared to other elite occupations the intergenerational immobility of professors was not especially high, but their marriage immobility was exceptional. Cultural capital theory receives more support than the meritocracy thesis. We hope that Mandemakers, Mandemakers and Mandemakers will accept the challenge and investigate whether these findings can be generalized to contemporary society.